FACTORS INFLUENCING HAND HYGIENE COMPLIANCE IN HYGIENE STAFF AT GRHASIA YOGYAKARTA HOSPITAL - Mahdar, Mahdar; Sukesi, Tri Wahyuni; Ruliyandari, Rochana (LPPM Univ. Ibn Khaldun Bogor, 2024)
Hospitals are health facilities that provide outpatient and inpatient services to patients. In addition, hospitals can be a source of infection transmission for staff, patients, and other visitors. To prevent nosocomial infections in health workers, hospitals have the responsibility to protect all health workers, one of the efforts is to implement hand hygiene practices. Hand hygiene compliance in hospital settings in particular is influenced by several factors, including predisposing, enabling, and reinforcing elements, as well as support from management and the chief hygienist. The purpose of this study was to determine the relationship between predisposing, enabling, and reinforcing factors. The method used was quantitative correlation with a cross-sectional approach. The population of this study were 36 janitors, with a sample size of 36 respondents who were still active as janitors at Grhasia Hospital. Sample selection using the Total sampling method, using an analysis system carried out using Chi-Square. From the results of the bivariate test, there were the results of the highest number of respondents with early adult age as much as 63.9%. Gender 97.2% p-value 1000. Tenure is 80.6% p-value 0.163. Education as much as 97.2% p-value 1000. Good knowledge as much as 75% p-value 0.255. Positive attitude 58.3% p-value 0.626. Complete facilities 86.1% p-value 0.466. Motivation 58.3% p-value 1000. so that with these results there is a relationship between age, gender, tenure, education, attitude, facilities and motivation with an α value <0.05. While the results of the multivariate test obtained the results Age, tenure and attitude have a great opportunity to increase hand hygiene compliance in janitors. Hand hygiene compliance in janitors can be influenced by the age of janitors, length of service and positive attitudes in janitors.